Audio-Visual Translation Techniques: Subtitling and Dubbing of Movie Soundtrack in Frozen: Let it Go - Moh Supardi; Dea Amanda Putri (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2018)
This article is aimed at finding out the technique of subtitle and dubbing translation in OST Frozen: Let it Go. The article analyzes the lyrics of the song as the corpus. The data are analyzed qualitatively by using the subtitle translation techniques. The data collection is conducted through reading source language and target language, selecting and comparing the translation techniques done by the translator/dubber, marking, classifying and analyzing them based on the theories of translation technique proposed by Molina and Albir. The result shows that subtitle techniques done by the translator consist of eleven techniques. Based on the analysis of translation process translated from the lyrics into the subtitled version, the translator seems to use most of the technique. While the dubber only uses nine techniques in translating the lyrics into the dubbed version. In general, the translator’s technique applied in the subtitled version is mostly literal translation; While the dubbed version’s most common techniques are modulation and reduction.—Artikel ini bertujuan untuk mengetahui tentang teknik penerjemahan subtitle dan dubbing dalam OST Frozen: Let It Go sebagai korpusnya. Data dianalisis secara kualitatif dengan menggunakan teknik terjemahan subtitle. Pengumpulan data dilakukan melalui proses membaca bahasa sumber dan bahasa target, memilih dan membandingkan teknik penerjemahan yang dilakukan oleh penerjemah / dubber, menandai, mengklasifikasi dan menganalisisnya berdasarkan teknik penerjemahan yang diajukan oleh Molina dan Albir. Hasilnya menunjukkan bahwa teknik subtitle yang dilakukan oleh penerjemah terdiri dari sebelas teknik. Berdasarkan analisis proses terjemahan yang diterjemahkan dari lirik ke dalam versi subtitle, penerjemah tampaknya menggunakan sebagian besar teknik. Sedangkan dubber hanya menggunakan sembilan teknik dalam menerjemahkan lirik ke dalam versi yang dijuluki. Secara umum, teknik penerjemah yang diterapkan dalam versi subtitle sebagian besar adalah terjemahan harfiah; Sementara teknik yang paling umum dijuluki versi adalah modulasi dan reduksi.